Beyond humanity? the ethics of biomedical enhancement - Buchanan, Allen E., 1948- (Oxford : Oxford University Press, 2011)
Biotechnologies enable us to be smarter, have better memories be stronger and quicker, live longer, be more resistant to diseases, and enjoy richer emotional lives. Buchanan explores urgent ethical issues raised by these developments, about what it is to be human and what sort of society we should strive to have.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Medical innovations -- Moral and ethical aspects